2007
DOI: 10.1063/1.2756136
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electro-optical properties in gold nanoparticles doped ferroelectric liquid crystals

Abstract: Influential electro-optical and textural properties in the smectic C* phase have been observed using gold nanoparticles (Au NPs) in ferroelectric liquid crystals (FLCs). An application of mere 0.1V brings fivefold increase in optical tilt and doping creates a strong intrinsic field inside the sample generating high tilt and a reproducible observation of memory effect. The lowering of threshold voltage and the enhanced optical contrast is probably due to the interaction of electron wave oscillation in Au NPs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
88
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(88 citation statements)
references
References 31 publications
0
88
0
Order By: Relevance
“…6,7 The addition of gold NPs in ferroelectric liquid crystals ͑FLCs͒ has been reported earlier in order to observe low threshold and nonvolatile memory effect. 8,9 Zhang et al 10 observed the lowering of threshold voltage of CdS NPs doped 4-pentyl-4'-cyanobiphenyl ͑5CB͒ twisted nematic cells by 25%. The low power operation of vertically aligned LC by doping a minute amount of anatase TiO 2 -NPs have been observed by Lee et al 11 Zinc oxide ͑ZnO͒ has been employed in a variety of devices such as gas sensors, solar cells, luminescent materials, and transparent conducting coatings due to its wide range of optical and electrical properties.…”
mentioning
confidence: 99%
“…6,7 The addition of gold NPs in ferroelectric liquid crystals ͑FLCs͒ has been reported earlier in order to observe low threshold and nonvolatile memory effect. 8,9 Zhang et al 10 observed the lowering of threshold voltage of CdS NPs doped 4-pentyl-4'-cyanobiphenyl ͑5CB͒ twisted nematic cells by 25%. The low power operation of vertically aligned LC by doping a minute amount of anatase TiO 2 -NPs have been observed by Lee et al 11 Zinc oxide ͑ZnO͒ has been employed in a variety of devices such as gas sensors, solar cells, luminescent materials, and transparent conducting coatings due to its wide range of optical and electrical properties.…”
mentioning
confidence: 99%
“…More recently, the effects of GNRs on the nematic liquid crystal (NLC) matrixes have also been reported. 12 It was observed that GNRs form their own self assembling well ordered structures inside the LC matrix. A large change in the electro-optical properties of a polymer dispersed liquid crystal (PDLC) due to inclusion of 14 nm diameter GNPs has also been observed.…”
Section: Introductionmentioning
confidence: 99%
“…In the works [4,5], being based on studies of the optical characteristics inherent to the mixture of ANP with LC, it was shown that aggregation of ANP can be reduced if using LC that has a smectic phase. The change in the optical or electrooptical properties of ferroelectric LC, when introducing ANP, was considered in [6][7][8][9]. The influence of ANP on non-linear optical properties of LC was studied in [10].…”
Section: Introductionmentioning
confidence: 99%